Comparison Between All-Atom and Coarse-Grained Dynamics Simulations for Predicting Mechanical Properties of Proteins (Communications in Computational Chemistry, 2025)
In this work, we perform all-atom and coarse-grained dynamics simulations to predict the mechanical properties of atypical synthetic protein system. Previous experiments showed that proteins with a larger molecular weight exhibit bettermechanical performance. Our steered molecular dynamics (SMD) simulations at the all-atom level only capture intermolecularinteractions and fail to reproduce this tendency. The results of the dissipative particle dynamics (DPD) simulations at the coarse-grained level are consistent with experiments. The comparison between two levels of resolution highlights the importance ofsimulation scales in predicting mechanical properties of complex systems. We also reveal some underlying factors correlated withthe mechanical properties of synthetic proteins, such as molecular weights, fabrication processes, the ratio of hydrophobic tohydrophilic segments and their order in the amino acid sequences.
Keywords: steered molecular dynamics; dissipative particle dynamics; mechanical property; silk protein; multiscale simulation